2007
DOI: 10.1159/000102999
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of the Radiological Evaluation of Nephrocalcinosis

Abstract: Background/Aim: The level of agreement concerning the diagnosis of nephrocalcinosis (NC) based on ultrasonography (US), computed tomography (CT) or kidney/ureter/bladder (KUB) X-ray was assessed. Methods: Sequences of KUB+US+CT from 62 patients, 48 with at least one exam suggesting NC and 14 with pelvicalyceal calcifications (nephrolithiasis) were reviewed twice by 3 radiologists (firstly randomized and secondly presenting KUB+US+CT of each patient together). Results: The intraobserver concordance varied from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
1
15
0
5
Order By: Relevance
“…Hypercalciuria was not detected. A previous evaluation of 444 patients with nephrolithiasis and without ADPKD in our service (19) revealed 58% of hypercalciuria, 53% of hypocitraturia, 23% of hyperuricosuria, and Ͻ1% of hyperoxaluria; therefore, this sample of patients with ADPKDϩLIT presented a unique metabolic profile showing no hypercalciuria, 18% of hyperoxaluria, and the same figures of hypocitraturia (approximately 50%) when compared with patients with nephrolithiasis and without ADPKD. The reasons for a higher percentage of hyperoxaluria and the lack of hypercalciuria in this sample, as in other series (2) as well, are not clear.…”
Section: Discussionsupporting
confidence: 49%
“…Hypercalciuria was not detected. A previous evaluation of 444 patients with nephrolithiasis and without ADPKD in our service (19) revealed 58% of hypercalciuria, 53% of hypocitraturia, 23% of hyperuricosuria, and Ͻ1% of hyperoxaluria; therefore, this sample of patients with ADPKDϩLIT presented a unique metabolic profile showing no hypercalciuria, 18% of hyperoxaluria, and the same figures of hypocitraturia (approximately 50%) when compared with patients with nephrolithiasis and without ADPKD. The reasons for a higher percentage of hyperoxaluria and the lack of hypercalciuria in this sample, as in other series (2) as well, are not clear.…”
Section: Discussionsupporting
confidence: 49%
“…Combined ultrasonography with CT had higher sensitivity (92%) and specificity of 89%, but there was lower concordance between CT and ultrasonography, making the radiologic diagnosis of nephrocalcinosis a challenge. 3 What is the pathophysiologic explanation of calcium deposition in the kidney? The exact pathogenesis of calcium deposition in nephrocalcinosis remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that the radiologist’s ability to detect NC is often not accurate 12,13 . The most sensitive radiological tool to detect NC is computed tomography and standard x-rays are used to follow the course of NC 14 .…”
Section: Discussionmentioning
confidence: 99%